Socioeconamic and Political Dynamics in Ibn Khaldun’s Thought (American Journal of Islam and Society, 1999)
This article explores Ibn Khaldun’s theories and ideas about the causesthat lead to the rise and decline of civilizations. By emphasizing thedynamic and interdisciplinary character of Ibn Khaldun’s methodology,it systematically shows how moral, social, political, economic, geographical,and cultural factors find their appropriate place in IbnKhaldun’s schemata. Unlike other studies of Ibn Khaldun’s contributions,this article recasts his ideas in contemporary terminology and atonce making Ibn Khaldun’s analysis and prescriptions relevant. Thearticle also examines the central role of welfare, justice, and developmentin statecraft, and provides a lucid model of a contemporaryIslamic welfare state whose muqusid include the material and moralwell-being of its citizens.